Peningkatan Hasil Belajar Passing Bawah Permainan Bola Voli Siswa Menggunakan Media Bola Modifikasi - Anton Anton (Publikasi Indonesia, 2023)
Classroom Action Research (PTK) was conducted to know the effectiveness of using ball modification media in class VIIA students of SMP Negeri 3 Teluk Keramat, Sambas Regency in improving learning outcomes of passing under volleyball in the 2018/2019 academic year. Research conducted by researchers using class action research methods (classroom action research). Classroom Action Research is a reflective study, which is carried out by action actors to increase the rational stability of their actions in carrying out tasks and deepen their understanding of conditions in learning practice. The source of the data in this study was class VIIA students at SMP Negeri 3 Teluk Keramat, Sambas Regency, for the 2018/2019 academic year. The data collection technique in classroom action research is the student's underpass performance test and observation. The data analysis technique used in this study was descriptive comparative, namely comparing quantitative data from the initial study conditions, cycle I and cycle II with percentages. Based on the results of this study, it was concluded that modified ball feedback media in learning to pass under the ball will improve learning outcomes in class VIIA students of SMP Negeri 3 Teluk Keramat, Sambas Regency, in the 2018/2019 academic year. This can be seen from the results of the performance test from the initial study, of the 18 students who initially got 5 students 14.71% completeness, and for those who had not completed 29 students 85.29% increased in cycle I to 47.06% complete and 52.94 % incomplete and in cycle II 100% completed with the percentage of students who scored 80-89, namely 41.18% and students who scored 90-100, there was 58.82%. The conclusion of the classroom action research is that the ball modification learning media improves the learning outcomes of volleyball underhand passing in class VIIA students. Teluk Keramat Public Middle School 3, Sambas Regency, for the 2018/2019 Academic Year. Based on the results of the classroom action research conducted, the researchers concluded that learning physical education, sports and health volleyball game material using modified ball learning media can improve the learning outcomes of underclass VIIA students at SMP Negeri 3 Teluk Keramat. This can be seen when the evaluation is carried out in each cycle and there is an increase in cycle 2. Based on the results of the researchers' observations during the initial process, from learning activities to evaluation, the researchers concluded that there was an increase in learning outcomes for passing under volleyball in each cycle.